Zmiany w funkcjonowaniu placówek leczenia i wsparcia osób uzależnionych od nielegalnych substancji psychoaktywnych podczas pandemii COVID-19 w ocenie i doświadczeniach pacjentów miasta Gdańska - Mielczarek, Jagoda (Progress. Journal of young researchers, 2024)
Researches in various fields of science have been interested in the problemof substance abuse since the first half of the 20th century, but the need for newsolutions seems to be endless – the current knowledge has to be constantly re-viewed and improved. Modern world reality poses new challenges in subjectof substance abuse, one of them being the pandemic crisis. In this study I pre-sent how the treatment and support system for addicted works during thatperiod. Various forms of remote treatment have been introduced in responseto the pandemic restrictions. In the study I have focused on the changes withdirect impact on the treatment of the recipients. Deriving out of subjective per-spective I try to examine how the respondents evaluate changes in the supportsystem forced by pandemic restrictions as part of their own therapeutic pro-cess. The conclusions are based on an empirical qualitative study using the tech-nique of open in-depth interview. The obtained data indicate that an onlineform of individual therapy and group activities may be beneficial in some par-ticular cases. Therefore, the situation of the COVID-19 pandemic may contributeto the improvement of the process of treatment offered by institutions. Pointingout the needs of respondents, the study I have conducted could indicate the di-rection of changes that may improve the quality of the support provided. Thispaper might be a contribution to the wider research on online forms of commu-nication and its appliances to the system of treatment and support for addicted.